Study on the Causes and impact of migration in garo people lifestyle - Mohammed Rokonuzzaman; M.T.N. Shimul; Shaikh Shamim Hasan; Md. Arifur Rahman Khan; Jaber Rana; Md. Abdullahil Bhuiyan (Turkish Journal of Agriculture: Food Science and Technology)
Garo people are tribal communities who live in the middle northern part of Bangladesh from time immemorial. The purpose of the research was to identify the reasons, outline, and impact on the relocation of Garo people in the city areas in Bangladesh. Primary data were collected from face-to-face contact through an interview schedule. The findings indicate that poverty, lack of production, unemployment, and security were the main push factors where urban job opportunity, urban life style and social security were pull factors for garo migration. Pattern analysis showed that 69 percent of respondents migrate to the city without a plan. Large farm and family size discourged the unplanned migarion where deteriorate social security influence garo people for unplanned migration. Study also revealed that garo people access to better income, health facility, transportation have increased. In contrast, the involvement of agricultureal activity greatly reduced. Moreover, migrated family maintain their daily requirement for food by purchasing market. Government should take policy for improving the security, income opportunity, and infrastructure for discouraging the unplanned migration from village to town.